Comparative Study of Ondansetron Verses Palonosetron in Cisplatin Induced Nausea Vomiting - Todi, Dr. Sreya (International Journal of Innovative Research in Medical Science, 2018)
Objective: Nausea and vomiting can adversely affect the life of a patient with cancer both during and after chemotherapy. A common side effect of Cisplatin regimens is severe nausea and vomiting. Cisplatin based regimens for cancer is categorized as highly emetogenic chemotherapy. There is considerable progress in the control of nausea and vomiting from those early days but there is still paucity of data on antiemetic regimens for patients undergoing multiday Cisplatin based regimens. Palonosetron differs from first-generation 5HT3 antagonists. It has a longer half-life and a 100-times greater binding affinity to the 5HT3 receptor. This prospective study was designed to compare the efficacy of antiemetics Ondansetron and Palonosetron to prevent Chemotherapy induced nausea vomiting (CINV) in cancer patients on Cisplatin regimens. Material and Methods: A prospective randomised study was conducted at the department of Oncology at a tertiary care centre. A total of 40 chemotherapy naïve patients were enrolled in the study; 20 each in the ondansetron and palonosetron groups. All patients received Cisplatin in a dose of at least 50 mg /sq meter of body-surface area. The severity of nausea was recorded and vomiting was recorded in terms of number, frequency and time to rescue medication. Results: Of 40 patients with cancer placed on chemotherapeutic regimens containing Cisplatin 20 were placed in the Ondansetron arm and 20 were placed in the Palonosetron arm. Mean age in Ondansetron group was 54±13.84 and in Palonosetron group was56±11.93. Out of 20 patients in ondansetron group mean vomiting was 6.4 times while in Palonosetron it was 4.2. In Ondansetron group 14 (70%) showed response to Ondansetron while in Palonosetron 16 (80%) showed response. There was no response to treatment in 6 (30%) in Ondansetron and 4 (20%) in Palonosetron. Palonosetron given daily from Day 1 up to Day 5 of chemotherapy significantly reduced the incidence of nausea on. Conclusion: The overall complete response (CR) rates of Palonosetron were slightly higher than the Ondansetron. Palonosetron can reduced the incidence and severity of nausea and vomiting who are on Cisplatin therapy as compared to Ondansetron